Practical Media Using Real Products in Bandung State Polytechnic for Manufacturing - Gamawan Ananto (Department of Mechanical Engineering Atma Jaya Catholic University of Indonesia, 2014)
In Bandung State Polytechnic for Manufacturing (Polman), like other vocational education institution, practical program in its workshop had the aim to build students skill competencies. For those, number of items in a structured exercise is created, combined with the real products from industrial collaboration that gave the benefits for both parties, such as fund generating for operation costs. Jobshop is the interesting type of products for the students due to its variety challenges, used the ‘process group’ layout that had advantages for variety requirements, and its appropriateness with practical media work. Jobshop items are normally initiated by inquiry or demand. Many projects may confirmed in the short term of time, or could be only few demands on the other period. Therefore this jobshop had the machine load fluctuation consequence regarding variety process needed and inquiries dependence. Minimizing such fluctuation, Batch Product could be combined for buffering media work and keep the education program machiningoperation is running due to Batch certain demand and time. Regarding the characteristic differences between jobshop and batch –that used ‘product group’ layout– related with competency that the students should get, creating batch area separately caused better timeschedule and order handling properness. It also encourages the student practical product spectrum wider since its comprehensive activities in each area and more focus execution of all involved parties to each kind of jobs. The other important thing is that order handling arrangement should be well planned and prepared. Any inquiries must be handled with good coordination in the organization professionally regarding the QCD necessity in the real production activity.